2009
DOI: 10.1016/j.jpeds.2008.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and TV Viewing Are Related to Less Bone Accrual in Young Children

Abstract: Objective-To examine the relation between baseline fat mass and gain in bone area and bone mass in preschoolers studied prospectively for 4 y, with a focus on the role of physical activity and TV viewing.Study design-Children were part of a longitudinal study in which measures of fat, lean and bone mass, height, weight, activity, and diet were taken every 4 months from ages 3 to 7 y. Activity was measured by accelerometer, and TV viewing by parent checklist. We included 214 children with total body dual energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 38 publications
1
39
0
1
Order By: Relevance
“…9 They were evaluated every four months over a five-year period, yielding up to 13 visits per child. 24 The protocol was approved by the IRB and written informed consent was obtained from the guardian. Age, sex, race/ethnicity, and household income were collected from the parent, and height and weight were measured each visit.…”
Section: Methodsmentioning
confidence: 99%
“…9 They were evaluated every four months over a five-year period, yielding up to 13 visits per child. 24 The protocol was approved by the IRB and written informed consent was obtained from the guardian. Age, sex, race/ethnicity, and household income were collected from the parent, and height and weight were measured each visit.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, despite the age-related impact of fat mass in females, menarche may modify this relationship, suggesting that hormonal changes during puberty may additionally affect fat-skeletal interactions [68]. Others have suggested that the negative impact of adiposity on skeletal development may happen prior to puberty [77, 78], and that the negative impact of childhood and adolescent obesity on bone persists through the post-pubertal years and into early adulthood [79]. …”
Section: Longitudinal Impact Of Fat Mass On Bone Health During Skeletmentioning
confidence: 99%
“…Inadequate weight-bearing exercise has been associated with slower bone accrual in children. [18][19][20] Children and teens who engage in predominately sedentary indoor activity may be at unique risk of low BMD by compromising both vitamin D exposure and weight bearing.…”
mentioning
confidence: 99%